Infection dynamics of two renal myxozoans in hatchery reared fry and juvenile Atlantic cod Gadus morhua L. - Holzer, Astrid S; Stewart, S; Tildesley, Andrew; Wootten, Rodney; Sommerville, Christina (Parasitology, 2010)
In order to study the infection dynamics of 2 renal myxozoans, Zschokkella hildae Auerbach, 1910 and Gadimyxa atlantica Køie, Karlsbakk and Nylund, 2007 in cultured Atlantic cod, Gadus morhua L. aged 3–19 months, a specific single-round PCR assay and a double-label in situ hybridization protocol were developed. The results demonstrated that the 2 myxozoans show spatial separation of their development with regard to spore formation inside the renal tubules versus the collecting ducts and ureters, as well as temporal separation with Z. hildae proliferating and developing spores only once the G. atlantica infection decreases, despite the presence of both myxozoans in the smallest fry studied. These results strongly suggest within-host competition of the 2 myxozoans with potential suppression of Z. hildae by G. atlantica until G. morhua acquires immunity against G. atlantica. The quantification of the G. atlantica infection inside the renal tubules before and after a 29-day experimental growth performance study using fry from hatcheries with differing filtration systems showed that the intensity of infection with G. atlantica seems to be controlled if prolonged exposure to the myxozoan transmission stages takes place from hatching onwards. Surprisingly, growth rates in the trial were inversely affected suggesting that G. atlantica does not negatively influence cod fry growth performance.